Effects of replacing zinc oxide with different levels of zinc lactate on growth performance, serum indexes, intestinal health and gut microbiota in weaned piglets - Dai, Fawen; Zhao, Fei; Huang, Xia; Jin, Muqu; Zhou, Qin; Lin, Tao; Zuo, Jianjun; Zhu, Yongwen (Frontiers in Microbiology, 2025)
IntroductionThis study evaluated the efficacy of substituting zinc oxide (ZnO) with varying levels of zinc lactate (ZnL) in weaned piglets.MethodsA total of 128 Duroc × Landrace × Yorkshire (DLY) weaned piglets (7.31 ± 0.25 kg) were randomly divided into 4 dietary groups for 18 days (n = 4 in each group): CON-(basal diet, no ZnO); CON+, basal + 1500 ppm zinc with ZnO; TRE1 (basal + 600 ppm zinc with ZnL); TRE2 (basal diet + 800 ppm zinc with ZnL).ResultsTRE2 achieved comparable growth performance (average daily gain, average daily feed intake, and feed intake to gain ratio) to CON+ (P > 0.05), while both showed significantly lower average diarrhea rates than CON- (P < 0.05). The skin redness scores in TRE1 (P > 0.05) and TRE2 (P > 0.10) were higher than CON+ on day 7 of the experiment. Supplementation with 800 ppm ZnL enhanced antioxidant capacity, increasing serum glutathione peroxidase (GPx), superoxide dismutase (SOD), copper-zinc superoxide dismutase (Cu/Zn-SOD) activities compared to CON- (P < 0.05), matching CON+ levels. TRE2 significantly increased the duodenal and jejunal villus height compared to CON- (P < 0.05), similar to CON+, and elevated duodenal/ileal mRNA expression of Claudin-1 compared to both controls (P > 0.05). Cecal microbiota analysis (16S rRNA) revealed that CON+ and TRE2 significantly reduced richness indices (Ace, Chao, and Sobs; P < 0.05) and increased the Simpson diversity index (P < 0.05) versus CON-. Compared with CON-, CON+ significantly increased proportions of genera Clostridium_sensu_stricto_1 and Streptococcus (P < 0.05) while decreasing [Eubacterium]_ruminantium_group (P < 0.05). TRE2 also had significantly reduced proportions of Christensenellaceae_R-7_group, Ruminococcus and [Eubacterium]_ruminantium_group (P < 0.05). Spearman correlation analysis revealed a significantly positive correlation between Clostridium_sensu_stricto_1 and serum SOD (P < 0.01), as well as between [Ruminococcus]_gauvreauii_group and GPx (P < 0.05). In contrast, Clostridium_sensu_stricto_1 was significantly negatively correlated with serum malondialdehyde (P < 0.01).DiscussionIn conclusion, dietary supplementation of 800 ppm zinc from ZnL achieved equivalent effects to 1500 ppm ZnO in enhancing antioxidant capacity and gut health by regulating the gut microbiota, providing an effective zinc reduction strategy for weaned piglet nutrition.